A predictable tragedy : Robert Mugabe and the collapse of Zimbabwe - Compagnon, Daniel (University of Pennsylvania Press, 2011)
When the southern African country of Rhodesia was reborn as Zimbabwe in 1980, democracy advocates celebrated the defeat of a white supremacist regime and the end of colonial rule. Zimbabwean crowds cheered their new prime minister, freedom fighter Robert Mugabe, with little idea of the misery he would bring them. Under his leadership for the next 30 years, Zimbabwe slid from self-sufficiency into poverty and astronomical inflation. The government once praised for its magnanimity and ethnic tolerance was denounced by leaders like South African Nobel Prize-winner Desmond Tutu. Millions of refugees fled the country. How did the heroic Mugabe become a hated autocrat, and why were so many outside of Zimbabwe blind to his bloody misdeeds for so long? In "A Predictable Tragedy: Robert Mugabe and the Collapse of Zimbabwe" Daniel Compagnon reveals that while the conditions and perceptions of Zimbabwe had changed, its leader had not. From the beginning of his political career, Mugabe was a cold tactician with no regard for human rights. Through eyewitness accounts and unflinching analysis, Compagnon describes how Mugabe and the Zimbabwe African National Union-Patriotic Front (ZANU-PF) built a one-party state under an ideological cloak of anti-imperialism. To maintain absolute authority, Mugabe undermined one-time ally Joshua Nkomo, terrorized dissenters, stoked the fires of tribalism, covered up the massacre of thousands in Matabeleland, and siphoned off public money to his minions-all well before the late 1990s, when his attempts at radical land redistribution finally drew negative international attention. -- Book jacket.